The Evolution of E-Module Development in Secondary Education: A Systematic Review of Trends and Emerging Practices - Nurbaiti, Annisa; Situmorang, Robinson; Sarifah, Iva; Rahmadi, Imam Fitri (Jurnal Paedagogy, 2026)
This study aims to systematically examine the evolution of e-module development in secondary education between 2020 and 2024. Employing a Systematic Literature Review (SLR) method guided by the PRISMA 2020 protocol, the study explores emerging trends in instructional design, pedagogical frameworks, and technological integration. A total of 27 Scopus-indexed empirical studies were analyzed through four thematic lenses: disciplinary distribution, pedagogical approaches, levels of interactivity, and reported learning outcomes. Data were analysed using thematic analysis following Braun and Clarke (2006). The results reveal a pronounced STEM concentration (n = 23; 85.2%), with Physics and Chemistry dominating, while non-STEM disciplines account for only 14.8% (n = 4). Constructivist pedagogies, particularly Problem-Based Learning (n = 8; 29.6%), are dominant, effectively supporting higher-order cognitive outcomes such as Critical Thinking Skills (n = 12; 44.4%). However, Collaboration Skills receive critically minimal attention (n = 1; 3.7%), revealing a systematic gap in addressing social learning competencies essential to 21st-century education. These findings establish e-modules as effective digital frameworks when researchers align pedagogical design with technological affordances. Two urgent recommendations emerge: first, researchers must investigate e-modules in non-STEM disciplines; second, future studies must prioritise collaborative features to address the critical gap in 21st-century skill development.